PENGUATAN KAPASITAS KELOMPOK TANI HARJO DAN TANI RAHAYU DALAM KOMPUTERISASI PENDATAAN PETANI - Rosa Delima; Joko Purwadi; Halim Budi Santoso; Argo Wibowo (Politeknik Negeri Sriwijaya, 2019)
Organic Agriculture is an important economic sector in Indonesia. Internal Control System (ICS) is an important part to guarantee organic product that farmer produce. To gain organic quality assurance certificate, it is needed computerized data of farmer and farmer activity. This computerized process will be an important issue for Farmer Union Organization (Kelompok Tani), especially for Tani Harjo Farmer Union Organization and Tani Rahayu Farmer Union Organization. Those two farmer unions process the farmer data manually. Tani Harjo and Tani Rahayu face the low ability to use computer and internet. Thus, it will be an obstacle in the process of computerization. Based on those problems, this empowerment activity will be focused on accompaniment of two farmers union, Tani Harjo and Tani Rahayu, to collect the data and processed it in the computer. The processes includes improvement capacity in computer usage, gathering the data from farmers, and store the data to computer. Participatory method and system deployment are used in this empowerment activity. Participatory method is used to identify and strengthen community in implementing and applying computer. System deployment is used to entry data to the system that already developed. The result for this activity is an computerized farmer data, agricultural field, and farming activities which has been done by farmer of Tani Harjo and Tani Rahayu.